The Correlation Between the Bureaucratic Reform and Performance Achievement: A Case Study at the Statistics Indonesia - Randy Pratama Lumenta; Abdullah Said; Irwan Noor (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
This study investigates the correlation between bureaucratic reform and performance due to conflicting theories about existing phenomena. In theory, it is posited that implementing bureaucratic reform should enhance performance by addressing various bureaucratic issues, resulting in a positive or directly proportional correlation. However, empirical evidence indicates persistent problems in bureaucratic performance, including public service-related complaints and other issues within the government. The government's proclamation of bureaucratic reform is expected to address these existing problems and facilitate the realization of Indonesia's goal of establishing a world-class government. Understanding the correlation between bureaucratic reform and performance achievement is crucial for designing effective programs to achieve the goals of bureaucratic reform. Given that certain conditions regarding bureaucratic reform within the work units of BPS (Statistics Indonesia) have not yet received national recognition, examining the correlation between bureaucratic reform and performance achievement is of utmost importance for BPS. A quantitative approach with correlation analysis was employed as the analytical method. The study's results reveal a positive correlation between bureaucratic reform and performance achievement, albeit not highly intense. This suggests that the variation in performance, which can be attributed to the implementation of bureaucratic reform, is not highly significant. Consequently, it becomes apparent that other factors beyond bureaucratic reform substantially influence performance at BPS. Therefore, BPS must optimize the implementation of bureaucratic reform to enhance productivity and attain superior performance.